APLIKASI BUNGKIL INTI SAWIT MELALUI PEMBERIAN ENZIM RUMEN DAN FERMENTASI SEBAGAI BAHAN PAKAN IKAN NILA BEST (Oreochromis niloticus) - Putri, Nadisa Theresia; Santoso, Limin; Samsudin, Reza (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2013)
An important factor on tilapia aquaculture (Oreochromis niloticus) is the availability of food in sufficient quantity, unfortunetely soybean meal and fish oil as feed ingredients are imported. Alternative feedstuffs needed to solve the problem of limited soybean meal. Indonesia is the largest producer of palm oil by-product called palm kernel meal (PKM). The study was conducted to determine the effect of the addition of rumen enzyme and fermentation on nutrient digestibility determines the level of PKM and PKM as a feed ingredient for tilapia growth. This research used completely randomized design with 7 treatments and 3 replications. BEST tilapia with total weight of 23.83 ± 1.39 g / fish were used. Data were analyzed using analysis of variance and followed by Duncan test. The study shows that the use of BIS fermented with rumen enzymes and Trichoderma reesei provide the best nutrition and digestibility compared to other treatments. Nutrient content and digestibility of total protein (83.73%), carbohydrate (65.46%), energy (77.77%) and total digestibility (58%).